(3fXQjI h JMdjd aj Ohd YQHjI eNJGQIs - (3gOj RhjQ eNda(B, (3GdOYejs; (3YOfGf OGhO eMeO GdYPGQj(B, s ((3YeGf(B:s (3OGQ LQjQ(B,s, 2010)
(3hGbY GdJfejI GdHTQjI h eaGgjegG , GdJfejI GdHTQjI COdI h eDTQGJ , GdGbJUGO GdeYQaj eaGgje h JGQjN , eDTQGJ h echfGJ GdGbJUGO GdeYQaj , YdGbI GdGbJUGO GdeYQaj HGdJfejI GdHTQjI , GdGbJUGO GdeYQaj h GdJfejI GdHTQjI h CKQgeG Ydi GdGfJGL h GdGfJGLjI GdHTQjI , MbjbI GdGbJUGO GdeYQaj aj hWffG GdYQHj , OhQ GdJfejI GdHTQjI aj GdhWf GdYQHj GdOhd GdefJNHI(B).s
(3eQGLY U(B.191s
Keywords: (3GdEbJUGOs; (3GdEbJUGO(B- (3GdeYQaIs; (3GdJfejI GdHTQjIs